(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: The purpose of this research is to assess regulatory, organizational and methodological documents, as well as Russian and international recommendations, to use infromation from them to identify and systematize problems in prevention of chronic non-communicable diseases, and tooffer solutions. Materials and Methods: Analysis encompasees the key Federal Laws of the Russian Federation; orders, records, and reports provided by various ministries and departments of the Russian Federation,as well as by the leading research institutes; guides, manuals, and federal recommendations; the latest Russian and foreign guidelines and recommendations on prevention of chronic non-communicable diseases. Results and Discussion: Analysis was faced with a number of problems:poor correlation between changes in regulatory documents governing the prevention of chronic non-communicable diseases; incomplete allowance for international experience and guidelines on prevention of chronic non-communicable diseases, incomplete epidemiological data; poor coordination and uneven assignment of responsibilities in structures involved in prevention; shift in emphasis from population-oriented prevention and high-risk groups towards secondary prevention; below-satisfactory efficiency of tuberculosis screening in clinical examination. Conclusions: Their resolutionmay significantly increase the effectiveness of measures intendedfor prevention of chronic non-communicable diseases and their risk factors from occurence in Russia. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.353-367